Morphometry of fresh paramphistomids (Trematoda: Digenea) collected from local abattoir in Chachapoyas, Amazonas, Peru - Cueva-Rodríguez, Medali (2022)
The aim of this study was to determine the morphological dimensions of adult paramphistomids collected at the local abattoir of Chachapoyas, Amazonas, Peru. The samples were collected in September 2017. Forty adult parasites of uniform size were selected and subjected to oviposition using the Dinnik and modified Dinnik techniques. Thirty eggs were randomly selected. Upon evaluation, the adult parasite in the fresh state has a reddish colour, more intense at the anterior and posterior ends, with a conical and ventrally curved body. The specimens measured 8.85 mm long, 2.27 mm wide, 0.32 mm anterior sucker and 0.60 mm posterior sucker, and the dimensions of the eggs were 126.91 µm long by 63.7 µm wide. The values obtained belong to a parasite of the Paramphistomidae family, compatible with Calicophoron microbothrioides.